Polymeric and non-polymeric nanofiber of Cinnamaldehyde from Cinnamon oil (Cinnamomum zeylanicum). (June 2020) - Moreta, S; Cahyono, E; Affandi, N D N; Fadil, F; Kurniawan, C
Abstract: Encapsulation of cinnamaldehyde within polymeric and non-polymeric-based nanofiber matrix was investigated. Polyvinyl alcohol (PVA) was used as a polymeric matrix, and β-cyclodextrin (CD) was used as a non-polymeric matrix. The study is aimed to purify cinnamaldehyde from cinnamon oil and to encapsulate it within the nanofibers matrix. The purification step was carried out using spinning band distillation. On the other hand, the nanofibers were prepared through electrospinning. Three different formula were made, namely PVA/cinnamaldehyde, PVA/β-CD/cinnamaldehyde 5% and PVA/β-CD/cinnamaldehyde 10%. The yield of isolated cinnamon oil was 0.26% with 88.90% cinnamaldehyde purity in fraction III tested using GC and GC-MS. In advanced, the SEM images indicate that the average diameter of the bare nanofiber matrix was 75 nm. The diameter was decreased in the presence of cinnamon oils in all samples (range 50-65 nm). The inclusion complex formation was confirmed from FTIR data in the presence of a band at 1700 cm-1 that indicate the presence of the aldehyde group in both polymeric and non-polymeric nanofibers matrix.